Mapping the Intersection of Education, Green Economy, and Green Jobs: A Bibliometric Analysis - Iqbal Faza Ahmad (Saneskara: Journal of Social Studies, 2026)
This study aims to explore the relationship between Education for Sustainable Development (ESD) and green jobs by mapping the scientific landscape of publications in the field. A bibliometric design was employed using Scopus data covering the period 2000–2025. The dataset consisted of journal articles and conference proceedings, analyzed with the Bibliometrix R-package to examine publication trends, citation performance, collaboration networks, keyword co-occurrence, and thematic evolution. The results indicate a steady rise in publications since 2010, with rapid growth after 2019 and a peak in 2024. Sustainable development and green economy emerged as core themes, while engineering education, green jobs, and curricula appeared as emerging areas of interest. The analysis also shows that the field is dominated by advanced economies such as China, the United States, and Finland, while Indonesia and other developing countries are beginning to play a more visible role. These findings imply that stronger integration of ESD into higher education and vocational pathways, supported by cross-country collaboration and curriculum innovation, is essential to prepare a workforce for inclusive and sustainable green transitions.